Answer:
0
Step-by-step explanation:
Plug in 11 for m. Remember to follow PEMDAS. First solve the parenthesis, then multiply.
m = 11
7(m - 11) = 7(11 - 11) = 7(0) = 0
0 is your answer.
~
Answer:
8
Step-by-step explanation:
When you subtract the 9-1=8
Answer:
b
Step-by-step explanation:
Answer:
10
Step-by-step explanation:
Answer:
see beleow
Step-by-step explanation:
Let's solve your equation step-by-step.
5.1+2.3x=23.5
Step 1: Simplify both sides of the equation.
2.3x+5.1=23.5
Step 2: Subtract 5.1 from both sides.
2.3x+5.1−5.1=23.5−5.1
2.3x=18.4
Step 3: Divide both sides by 2.3.
2.3x
2.3
=
18.4
2.3
x=8
Answer:
x=8